2019
DOI: 10.1002/mrd.23279
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization placenta overgrowth in mice is associated with downregulation of the paternal imprinting gene H19

Abstract: In vitro fertilization (IVF) is a widely used assisted reproductive technology for individuals with infertility that may cause placental maldevelopment, which is harmful to the future health of the offspring. In this study, using a mouse model, we not only revealed changes in the placenta caused by IVF at embryonic day 18.5 (E18.5), but also attempted to identify factors that correlate with IVF‐induced abnormal placental development. Our results demonstrate that IVF‐induced placental maldevelopment is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, H19 is the most studied allele in animal experiments involving processes such as ovulation induction and embryonic culture, and it has been investigated as a potential validation marker for epigenetic alterations in response to in vitro fertilization (IVF)/intracytoplasmic sperm injection [ 63 ]. One study provided new insights into the development of improved IVF procedures and the lifelong health of offspring by demonstrating that hypermethylation of the imprinted regulatory region of the H19-imprinted maternally expressed transcript is linked to IVF-induced placental dysplasia [ 64 ]. Considering that these abnormal methylation modifications may evade the demethylation process of the fertilized ovum and thus be passed down to future generations, resulting in illnesses, special precautions should be taken regarding potential epigenetic hazards during reproduction, particularly when utilizing ARTs.…”
Section: H19 and Assisted Reproductive Technology-related Pathologymentioning
confidence: 99%
“…Furthermore, H19 is the most studied allele in animal experiments involving processes such as ovulation induction and embryonic culture, and it has been investigated as a potential validation marker for epigenetic alterations in response to in vitro fertilization (IVF)/intracytoplasmic sperm injection [ 63 ]. One study provided new insights into the development of improved IVF procedures and the lifelong health of offspring by demonstrating that hypermethylation of the imprinted regulatory region of the H19-imprinted maternally expressed transcript is linked to IVF-induced placental dysplasia [ 64 ]. Considering that these abnormal methylation modifications may evade the demethylation process of the fertilized ovum and thus be passed down to future generations, resulting in illnesses, special precautions should be taken regarding potential epigenetic hazards during reproduction, particularly when utilizing ARTs.…”
Section: H19 and Assisted Reproductive Technology-related Pathologymentioning
confidence: 99%
“…IVF disturbs the DNA methylation of the imprinting control region of H19/Igf2 , Snrpn , Peg3 , and Kcnq1ot1 genes, inducing morphological alterations in the placenta and an increased risk of adult metabolic syndrome [ 86 ]. Studies using animal models have demonstrated a dysregulation of several maternally and paternally expressed imprinted genes (e.g., Kcnq1ot1 involved in placental growth, Peg10 that is required for the differentiation of placental spongiotrophoblast and labyrinth, Peg11/Rtl1 involved the development of placental labyrinth and nutrient passive transport, Sfmbt2 playing a key role in the maintenance of trophoblast cell types) in the IVF group as compared to the control group [ 87 , 88 , 89 ]. Most of these genes play an important role in the proper placental morphology and function.…”
Section: Pathophysiology Of the Placenta In Pregnancy Complications And Art Pregnanciesmentioning
confidence: 99%